Inovação pedagógica na formação acadêmica: a experiência de monitoria de inovação pedagógica no curso de Pedagogia - Santos, Regiane Alves dos (Universidade Federal do Tocantins, 2023)
The present work discusses in a theoretical and interpretative perspective the theme of 'Pedagogical Innovation in Academic Training, seeking to overcome the static model of transmitting knowledge, a simplistic and automatic view of academics that only reproduce, instead of building intellectual and attitudinal autonomy. The discussions that surround the theme involve the construction of scientific knowledge through Pedagogical Innovation, as an adjunct to the Institutional Program of Pedagogical Innovation (PIIP), in order to awaken in the academic community the protagonism and autonomy in the systematization of this knowledge, bringing the proposal of Pedagogical Innovation Monitoring as sustained practices in Active Learning Methodologies. Thus, through a survey with the Pedagogical Innovation Monitors, using the qualitative method, a commendable reflection arises: what contributions does the Institutional Program for Pedagogical Innovation (PIIP) bring to academic training? Presenting possible contributions of the PIIP from the Pedagogical Innovation Project (PIP) in the academic formation of the Pedagogy course at the Federal University of Tocantins, Miracema campus, becoming a propussor for new possibilities of study and learning conditions.